Competencies of Shariah Auditors: Skills, Knowledge, and Challenges in Islamic Banking Practice - Lathifah, Ridha Nur; Taufik, Razanah (Tazkia Islamic University College, 2025)
This study explore the competencies of Shariah auditors, which include technical skills (hard skills) such as understanding Shariah accounting standards and fiqh muamalah principles, as well as interpersonal skills (soft skills) such as communication, integrity, and objectivity. Using the literature review method, data was collected from recent journals and scientific reports. The results showed that these competencies are essential for ensure compliance with Shariah principles, manage risk, and enhance accountability in Islamic financial institutions. One of the main challenges faced is the lack of certified auditors and the need for continuous training. This research emphasizes the importance of competency development to support the sustainability of the Islamic banking industry.